Akses Informasi Literasi Keislaman Rohis di Indonesia: Analisis Konstruksi Keberagamaan - Muhammad Dalimunthe; Franindya Purwaningtyas (PERSPEKTIF, 2020)
This research was conducted in three major cities in Indonesia (Medan, Yogyakarta, and Makassar). The choice of location was based on the representation of high schools in Indonesia. These cities have different Rohis characteristics from other cities. This study aims to know access to Islamic information literacy among Rohis activists in Indonesia. Rohis became an important pillar in shaping the Islamic model in public schools because it was considered as a reference for Islam in schools. The research model used is qualitative, by analyzing in-depth data through the point of view of the informant through the FGD. The results showed that of the three cities sampled had different characteristics of Islamic information access. The cities of Medan and Makassar are more dominated by social media such as Instagram and Youtube. Also, Makassar has a popular local figure who is a source of reference. The city of Yogyakarta is more dominantly influenced by educational institutions, religious organizations, and local religious leaders that can be accessed directly. Models of access to information construct Rohis religious diversity and their views of different countries and people so that they tend to follow the religious model of the figures and sources of information that are most often accessed and consumed.